Beneficial Effects of GLP-1 Agonist in a Male With Compulsive Food-Related Behavior Associated With Autism - Järvinen, Anna; Laine, Merja K.; Tikkanen, Roope; Castrén, Maija L. (Frontiers in Psychiatry, 2019)
Individuals with autism spectrum disorder (ASD) frequently display intensely repetitive, restricted thoughts, and behaviors. These behaviours have similarities to compulsions and/or obsessions in obsessive compulsive disorder (OCD) and are primarily treated with behaviourally-based interventions and serotonin uptake inhibitors (SSRIs). Due to the lack of treatment responses in many cases, however, new treatments are being sought. Here we report beneficial effects of treatment with liraglutide, a glucagon-like peptide-1 (GLP-1) analog, on severe obsessive food craving, binge eating, weight gain, and behavioural problems in an adolescent male with infantile autism and moderate intellectual impairment. Liraglutide treatment reduced weight and unwanted behaviour seemingly by preventing food-related repetitive thoughts and compulsions. Our report provides clinical evidence that GLP-1 signaling pathway may represent a novel target for treating food-related behavioural problems and aggressive behaviour in ASD.